2010
DOI: 10.1158/1535-7163.mct-09-0407
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Enhances the Inhibitory Effects of Δ9-Tetrahydrocannabinol on Human Glioblastoma Cell Proliferation and Survival

Abstract: The cannabinoid 1 (CB 1 ) and cannabinoid 2 (CB 2 ) receptor agonist Δ 9 -tetrahydrocannabinol (THC) has been shown to be a broad-range inhibitor of cancer in culture and in vivo, and is currently being used in a clinical trial for the treatment of glioblastoma. It has been suggested that other plant-derived cannabinoids, which do not interact efficiently with CB 1 and CB 2 receptors, can modulate the actions of Δ 9 -THC. There are conflicting reports, however, as to what extent other cannabinoids can modulate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
132
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 36 publications
13
132
1
Order By: Relevance
“…Recent results by McAllister's group indicate that CBD, which had been previously shown to reduce the growth of different types of tumor xenografts by itself (21)(22)(23)25), enhance the inhibitory effects of THC on the viability of glioma cells (26). In line with this idea, in this report we find that the combination of submaximal doses of THC and CBD reduce tumor growth with a similar potency compared with an effective dose of THC.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Recent results by McAllister's group indicate that CBD, which had been previously shown to reduce the growth of different types of tumor xenografts by itself (21)(22)(23)25), enhance the inhibitory effects of THC on the viability of glioma cells (26). In line with this idea, in this report we find that the combination of submaximal doses of THC and CBD reduce tumor growth with a similar potency compared with an effective dose of THC.…”
Section: Discussionsupporting
confidence: 84%
“…22), a mechanism that seems to operate also in glioma cells (23,25). Of note, the combined administration of THC and CBD is being therapeutically explored (10,20,26), although its effects on the proliferation and survival of cancer cells have only been analyzed in vitro (26).…”
mentioning
confidence: 99%
“…CBD inhibits cancer growth and induces apoptosis by generating ROS and upregulating caspase proteases by inducing endoplasmic reticulum and mitochondrial stress, whereas ⌬ 9 -THC inhibition of cancer is CB1 and CB2 receptor-mediated and leads to the activation of MAPK/ERK pathways and ceramide accumulation. Thus, combining these mechanisms by using together CBD and ⌬ 9 -THC is likely to produce synergistic effects in several diseases (527). Indeed, in an animal model of MS spasticity, the indication for which Sativex is approved in more than 26 countries, this botanical drug is more efficacious at reducing limb spasticity than ⌬ 9 -THC alone, even though CBD is inactive in this test (356).…”
Section: Sativexmentioning
confidence: 99%
“…It has been shown that cannabidiol (CBD) exhibits antineoplastic activity in multiple GBM cell lines in culture and in xenograft mouse models (Massi et al, 2004(Massi et al, , 2006(Massi et al, , 2008Vaccani et al, 2005;Marcu et al, 2010;Torres et al, 2011;Nabissi et al, 2013;Solinas et al, 2013;Soroceanu et al, 2013). This antineoplastic activity is mediated through plasma membrane-associated receptors, including G protein-coupled receptor (GPR) 55 and transient receptor potential cation channel subfamily V member (TRPV) 1/2, and involves the production of reactive oxygen as well as induction of autophagy and apoptosis (Bisogno et al, 2001;Ligresti et al, 2006;Massi et al, 2006;Ford et al, 2010;Ramer et al, 2010;Yamada et al, 2010;Piñeiro et al, 2011;Anavi-Goffer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%